Comparison of peak expiratory flow rate (PEFR) before and after physical exercise in obese and non-obese children - Febrina Z. Siregar; Gabriel Panggabean; Ridwan M. Daulay; Helmi M. Lubis (Indonesian Pediatric Society, 2009)
Background Obesity has been associated with respiratorycomplications and it is believed to reduce lung volume. Obesityimposes additional stress on ventilation during exercise andmay even result in pulmonary function impairment. Exerciseinduced-bronchospasm has also been found in obese children.Lung function tests can be useful to confirm diagnosis, responseto therapy, or prediction of lung and respiratory diseases. Thepeak flow meter is an inexpensive, practical way to measure lungfunction, and can detect the early warning signs of a decrease inlung function.Objective To compare the peak expiratory flow rate (PEFR) beforeand after physical exercise in obese and non-obese primary schoolboys aged 6 to 12 years old.Methods A quasi-experimental study using the one group pretest-posttest design was performed on 30 obese children (BMI abovethe 95<h percentile) and 30 non-obese children (BMI betweenthe 5<h - 85'h percentile) using a mini-Wright peak flow meterto evaluate the PEFR before and after eight minutes of physicalexercise. Height, weight, body mass index, and physical statuswere determined before testing.Results The PEFR before and after exercise were 14.80 for obesechildren and 9.76 for non-obese children. The mean value forPEFR between obese and non-obese children was significantlydifferent (P<0.05).Conclusion The PEFR for obese children is significantly lowerthan non obese children even before physical exercise.